Investigations on the Outdoor Performance Characteristics of Multicrystalline Silicon Solar Cell and Module. (23rd May 2013) - Parthasarathy, Sivakumar; Neelamegam, P.; Thilakan, P.; Tamilselvan, N.
Abstract : Multicrystalline silicon solar cell and its module with 18 cells connected in series were mounted on an inclined rack tilted 12° South positioned at latitude of 12.0107° and longitude of 79.856°. Corresponding solar irradiance was measured using an optical Pyranometer. Measured irradiance, open circuit voltage (V oc ), and short circuit current (I sc ) values were analyzed.V oc values of both the cell and module were found saturated at above the critical value of illuminations which were different from each other. The integrated daily efficiency for the cell and module were ~10.25% and ~9.39%, respectively, that were less than their respective standard test condition's value. The reasons for this drop in efficiencies were investigated and reported.